Proceedings of the First International Conference on Administration Science (ICAS 2019) 2019
DOI: 10.2991/icas-19.2019.80
|View full text |Cite
|
Sign up to set email alerts
|

Causative Factors of Indonesia’s Rural Areas’ Low Funding

Abstract: Village funds management that is mandated in Law No. 6 of 2014 of Villages aimed to the development and empowerment of village people is still not optimal. This research purpose is to identify and analyze several factors that cause not optimal management of village funds. The method used is Bartlett test analysis factor, Kaiser-Mayer-Olkin (KMO), Measures of Sampling Adequacy (MSA), factor extraction using Principal Component Analysis (PCA), factor selection using Eigen values and Plot Cree, and factor rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Thus, young people not only generate income for themselves but also contribute to environmental cleanliness. According to Kania et al (2019) that the existence of BUMDes is not only an effort to implement government programs but also can be a solution to the economic problems of a village.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, young people not only generate income for themselves but also contribute to environmental cleanliness. According to Kania et al (2019) that the existence of BUMDes is not only an effort to implement government programs but also can be a solution to the economic problems of a village.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Rodiyah (2019) revealed that the BUMDes are business entities determined through village regulations made based on the results of village deliberations. The establishment of BUMDes is expected to be a solution for village economic problems by comprehensive handling, including the construction of infrastructure facilities, development of rural economic potential and optimization of potential for the welfare of rural communities (Kania et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the law, the village has the authority to manage its own assets, including the management of the village economy. The problems of village economic need to be resolved with comprehensive handling, including the construction of infrastructure facilities, the economic potential development of the village, and this potential optimization for the village communities' welfare (Kania, Akbar, & Budiman, 2019).…”
Section: Village-owned Enterprise (Bumdes)mentioning
confidence: 99%
“…Adapun informan dalam penelitian ini terdiri dari informan kunci (Key informan) Dinas KOMINFO Kabupaten Garut sebagai informasi awal yang memahami dan berkaitan b. Data Sekunder dimana sumber data penelitian yang diperoleh dalam bentuk yang sudah jadi atau melalui media perantara yang tersedia di lapangan (Kania et al, 2019). Seperti halnya buku-buku, jurnal, dokumen penelitian, foto, audio, dan laporan kegiatan.…”
Section: ) Sumber Dataunclassified